Design System pada Perancangan Antarmuka Perangkat Lunak Sistem Akses Digital - Apriansyah Rizqi Setiawan; Marsani Asfi; Agus Sevtiana; Sudadi Pranata; Willy Eka Septian (LPPM STT Terpadu Nurul Fikri, 2023)
In developing software systems, there were no rules for making interface patterns in web base applications. The problem is the inconsistency of design styles between software, and the interface design development process takes a long time. This study aims to produce a design framework called Access Digital Design System. The system development method approach used in this research is Atomic Design which has several stages adapted to the investigation. In this study, the design system built is limited to product elements consisting of functional patterns and perceptual patterns. This research will produce a design system made up of perceptual and available marks as output artifacts in the form of code libraries, style guides, and pattern libraries. Based on the study, the designed Design System can reduce time spent creating user interface designs by using component guidelines and documentation with standardized foundation elements to increase productivity. Additionally, the final interface design becomes more consistent and uniform.